Visual Simulation of Missile Attacking Battleplane Based on Vega - Xiong Fengguang; Han Xie; Zhang Huibing (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
A visual simulation system of fragment warhead missile attacking F-16C ''Falcon'' battleplane based on simulation and virtual reality technology is put forward. Firstly, the overall design of visual simulation of missile attacking F16 battleplane is implemented, and all functions of each module are demonstrated in detailed. Then 3D models in virtual battle field are optimized by level of detail, texture mapping, billboard and instance technology. Finally, Vega scene driving program is developed, and the implementation of special effect, view transform, preview and collision detect are emphasized. The result of simulation provides reference for damage assessment of missile attacking F16 battleplane. DOI : http://dx.doi.org/10.11591/telkomnika.v12i1.3941